Politics of temporalization : medievalism and orientalism in nineteenth-century South America - Altschul, Nadia (University of Pennsylvania Press, 2020)
"This book delves further into the politics of the medieval/modern divide and its attendant concepts of modernity, alternative modernities, and the premodern by investigating these historical boundary-crossing struggles in the Ibero-American context. The notion that Ibero-America was medieval or that the British Empire would bring modern ways of life to the Spanish American premodern backwaters was not the purview of twentieth- and twenty-first-century scholars but was already evident in early ethnographic and autoethnographic texts from the nineteenth century"--